Intellectual Property Management: European Universities Experience - A. Yu. Kalinin; Yu. V. Nechepurenko (Цифровая трансформация)
A comparative analysis of policies in the field of intellectual property (IP) of universities in leading European countries: Switzerland, the UK and the Netherlands. As a result of the comparison, the main components of these policies are identified as a single document: the purpose of the policy, the procedure for determining copyright holders, students' rights to IP, material incentives for using IP, and responsible structures. The policy of each university takes into account the features and traditions of its activities. It was revealed that each university has its own approach to material incentives for the creation and use of IP. The conditions are established under which the university does not claim to IP created by students. It is concluded that it is advisable to develop similar IP policies for Belarusian universities.